2009
DOI: 10.1098/rsif.2008.0538
|View full text |Cite
|
Sign up to set email alerts
|

A novel ataxia-telangiectasia mutated autoregulatory feedback mechanism in murine embryonic stem cells

Abstract: Ataxia-telangiectasia mutated (ATM) is known to play a central role in effecting the DNA damage response that protects somatic cells from potentially harmful mutations, and in this role it is a key anti-cancer agent. However, it also promotes repair of therapeutic damage (e.g. radiotherapy) and so frustrates the efficacy of some treatments. A better understanding of the mechanisms of ATM regulation is therefore important both in prevention and treatment of disease. While progress has been made in elucidating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…At both time points after irradiation, notably, the level of ATM was significantly decreased in cells over-expressing miR-27a. Besides the action of miR-27a on ATM -3′UTR, such mRNA reduction could be due to an ATM autoregulatory feedback mechanism in response to DNA damage, as recently proposed by Clyde et al [28]. According to these authors, cells have evolved a sensor mechanism that results in rapid induction of the ATM transcript to compensate for ATM chemical inhibition through a negative feedback.…”
Section: Resultsmentioning
confidence: 91%
“…At both time points after irradiation, notably, the level of ATM was significantly decreased in cells over-expressing miR-27a. Besides the action of miR-27a on ATM -3′UTR, such mRNA reduction could be due to an ATM autoregulatory feedback mechanism in response to DNA damage, as recently proposed by Clyde et al [28]. According to these authors, cells have evolved a sensor mechanism that results in rapid induction of the ATM transcript to compensate for ATM chemical inhibition through a negative feedback.…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, an effective approach would be to increase the radiosensitivity of tumors and improve therapeutic efficacy by promoting tumor cell cycle progression then arrest at G 2 /M phase. However, regulation of cell cycle is closely related to DDRs, and studies have shown that DDR signaling pathways are initiated well by phosphoinositide 3-kinase-like kinase family members, including ATM kinase and ataxia-telangiectasia and Rad3-related kinase, which recognize different types of DNA lesions 25. Importantly, it is well demonstrated that ATM kinase is activated by double-stranded DNA breaks (DSBs) induced by irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, regulation of cell cycle is closely related to DDRs, and studies have shown that DDR signaling pathways are initiated well by phosphoinositide 3-kinase-like kinase family members, including ATM kinase and ataxia-telangiectasia and Rad3-related kinase, which recognize different types of DNA lesions. 25 Importantly, it is well demonstrated that ATM kinase is activated by double-stranded DNA breaks (DSBs) induced by irradiation. In response to IR-induced DNA damage, ATM kinase is recruited to the sites of DSBs and is activated by autophosphorylation at Ser-1981 and binding to heterotrimeric Mre11/Rad50/Nbs1 adaptor complex, resulting in phosphorylation of downstream substrates such as Chk2 and p53 protein and eventually inducing cell cycle checkpoint activation to arrest cells at G 2 /M phase by initiating downstream cascade reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Under certain condi ons, however, the pa ern of expression of ATM may be altered, which is accompanied by a corresponding change in ATM ac vity [778][779][780]. ATM may be subject to transcrip onal regula on at promoter as well as at mRNA level [781][782][783]. ATM is one of the major targets of novel an cancer therapies.…”
Section: Irish Blessingmentioning
confidence: 99%